Gambaran tingkat kemandirian personal Hygien pada penderita kusta - Nisfil Mufida (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Personal hygiene is one of actiontomaintainthe clean lines sandhealthy of a personfor physical and psychological wellfare. Fulfillment ofpersonal hygiene required for individual comfort,safety, and health. Personal hygiene needed bothinpeople who is health and in people who is sick. Mostof the respondents had less personal hygiene. Thepurpose of this study is to describethe degree ofindependence of personal hygienein leprosypatients. This research method is descriptive withsurvey approach. The variable is leprosy personalhygiene. The number of samples is 15 respondentsof lepers. The sampling usingthe total population, theinstrument is a questionnaire.The results of the studymost of therespondents have less personalhygiene13 people (86.66%). Then, it can bedescribed that personal hygiene of lepers at theTangungguh village is notqualify inpersonal hygieneneeds. With the results of this study are expectedthat leprosy patients can understand about an effortin clean living to decrease leprosy. And for healthworkers and related institution related agenciesshould further expandthe study of efforts to increasepublic understanding of leprosy patient primarily onefortsinclean living. For further research canbeusedas a referencein the development ofsubsequentscientific work.